Effects of shear strength properties on electrical resistivity of compacted laterite soil: A conceptual model - Memon, M.B. (Asian Research Publishing Network, 2016)
Laterite soil is commonly considered as a good natural foundation and building material. This type of soil is found in abundance in most of the tropical countries including Malaysia. In any project, the properties of laterite soil are determined through borehole sampling which is the actual determination of the subsurface soil but on contrary it is very expensive and time consuming process and also requires too much effort. Therefore, in order to save cost, time and energy, electrical resistivity method is an alternative method which could provide quick and rapid assessment of the subsurface soil without causing any disturbance to the soil and thus much time and money could be saved. In this research paper, a conceptual model for the assessment of strength properties of compacted laterite soil has been proposed based on the correlations of soil properties mainly cohesion and angle of internal friction with electrical resistivity values. The results analyzed from the study hopefully will contribute for the possible assessment of the electrical resistivity method to be used for the determination of geotechnical properties of laterite soil in geotechnical calculations such as factor of safety (FOS) and bearing capacity. Â© 2006-2016 Asian Research Publishing Network (ARPN).